2005
DOI: 10.1002/cjce.5450830606
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Copper Oxide Impregnated HZSM‐5 in Methanol Conversion to Liquid Hydrocarbons

Abstract: M ethanol obtained from coal and natural gas can be used as a raw material for synthesis of methanol. Methanol is used as a raw material for the production of olefins and other hydrocarbons using zeolite catalysts. Zeolites such as HZSM-5 have attracted many researchers to obtain yield of gasoline range hydrocarbons. Its nature and extent of reaction depend on acid strength, acid site density, catalyst topology, temperature, pressure, space velocity and other process conditions (Alkawaldeh et al., 2003;Cañizar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Reducing the aromatic content in the produced fuels is very important to http address the global more strict environmental regulations. In the past few years, more continuous researches were reported on the modification of HZSM-5 by various metal oxide composites, such as CuO [21], ZnO/CuO [8] and Ga 2 O 3 [22,23], as well as acid or alkali treatment [2,24] in MTG process. Most studies revealed that the acidic properties and mesopore formation of ZSM-5 catalysts were well altered, and the diffusion properties of the pore channels were improved.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the aromatic content in the produced fuels is very important to http address the global more strict environmental regulations. In the past few years, more continuous researches were reported on the modification of HZSM-5 by various metal oxide composites, such as CuO [21], ZnO/CuO [8] and Ga 2 O 3 [22,23], as well as acid or alkali treatment [2,24] in MTG process. Most studies revealed that the acidic properties and mesopore formation of ZSM-5 catalysts were well altered, and the diffusion properties of the pore channels were improved.…”
Section: Introductionmentioning
confidence: 99%
“…Also, agglomeration of some metal particles on the outer surface of zeolite can cause similar effects. 46,47 According to Figure 2(a), the N 2 adsorption-desorption isotherms of all samples exhibit an incremental slope in lower relative pressures which could be attributed to the typed I isotherm with H 4 -shaped hysteresis loops indicating the presence of micropores in the structure of zeolites. But at pressures of 0.45 \ p/p0 \ 0.9, the hysteresis loops of the modified samples are more distinct than ZSM-5/11 zeolite, indicating mesoporosity increases after incorporation of metals.…”
Section: Bet Analysismentioning
confidence: 97%
“…This is crucial to increase the lifetime and efficiency of the catalyst. The research outcomes pointed out that direct glycerol thermochemical reaction is technologically feasible but hindered by catalyst coking that will poison the catalyst [77] and ineffective catalyst regeneration [62,78]. Table 3 explains the catalytic conversion of glycerol to different chemicals which are beneficial to us.…”
Section: Catalyst Design and Robustness?mentioning
confidence: 99%